Colloidal HgTe Quantum Dot/Graphene Phototransistor with a Spectral Sensitivity Beyond 3 µm. Issue 6 (1st February 2021) - Grotevent, Matthias J.; Hail, Claudio U.; Yakunin, Sergii; Bachmann, Dominik; Calame, Michel; Poulikakos, Dimos; Kovalenko, Maksym V.; Shorubalko, Ivan
Abstract: Infrared light detection enables diverse technologies ranging from night vision to gas analysis. Emerging technologies such as low‐cost cameras for self‐driving cars require highly sensitive, low‐cost photodetector cameras with spectral sensitivities up to wavelengths of 10 µm. For this purpose, colloidal quantum dot (QD) graphene phototransistors offer a viable alternative to traditional technologies owing to inexpensive synthesis and processing of QDs. However, the spectral range of QD/graphene phototransistors is thus far limited to 1.6 µm. Here, HgTe QD/graphene phototransistors with spectral sensitivity up to 3 µm are presented, with specific detectivities of 6 × 10 8 Jones at a wavelength of 2.5 µm and a temperature of 80 K. Even at kHz light modulation frequencies, specific detectivities exceed 10 8 Jones making them suitable for fast video imaging. The simple device architecture and QD film patterning in combination with a broad spectral sensitivity manifest an important step toward low‐cost, multi‐color infrared cameras. Abstract : Colloidal quantum dot/graphene phototransistors offer a viable alternative to traditional infrared detector technologies owing to inexpensive synthesis and processing of QDs. Here, the spectral sensitivity is extended up to 3 µm with HgTe QD/graphene phototransistors presenting specific detectivities of 6 × 10 8 Jones, and kHz operation demonstrating potential for fast video imaging.